2011
DOI: 10.1128/iai.00832-10
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Transport Contributes to Pneumococcal Colonization

Abstract: Streptococcus pneumoniae is a major cause of pneumonia and meningitis. Airway colonization is a necessary precursor to disease, but little is known about how the bacteria establish and maintain colonization. Carbohydrates are required as a carbon source for pneumococcal growth and, therefore, for colonization. Free carbohydrates are not readily available in the naso-oropharynx; however, N-and O-linked glycans are common in the airway. Sialic acid is the most common terminal modification on N-and O-linked glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 44 publications
4
100
0
Order By: Relevance
“…The genes satABC are required for both growth and transport of sialic acid and encode the substrate binding protein (satA) and two permeases (satBC). However, no predicted ATPases were identified in the satABC genetic locus (23). Because two ATPases are absolutely necessary for transport, this requires that a gene(s) encoding the ATPase to energize this transporter must be encoded elsewhere in the genome.…”
Section: Streptococcus Pneumoniae (Pneumococcus) Is An Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes satABC are required for both growth and transport of sialic acid and encode the substrate binding protein (satA) and two permeases (satBC). However, no predicted ATPases were identified in the satABC genetic locus (23). Because two ATPases are absolutely necessary for transport, this requires that a gene(s) encoding the ATPase to energize this transporter must be encoded elsewhere in the genome.…”
Section: Streptococcus Pneumoniae (Pneumococcus) Is An Importantmentioning
confidence: 99%
“…We have recently identified genes encoding components of the pneumococcal ABC transporter for sialic acid and have shown that it contributes to airway colonization (23). As free carbohydrates are scarce in the airway, S. pneumoniae likely utilizes complex glycans for growth (19).…”
Section: Streptococcus Pneumoniae (Pneumococcus) Is An Importantmentioning
confidence: 99%
“…NanA was shown to contribute to nasopharyngeal colonisation [41,43,68–70]. However, these findings contrast to several other publications, where no such effects were observed in vivo [28,55,71–73]. Apart from differences in the bacterial strains and challenge doses, the reliability of generating true isogenic mutant strains may be a concern, especially when using a bacterium like the pneumococcus that is notorious for its genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that intranasal inoculations of free sialic acid could increase the colonization of the nasopharynx in infected mice (22,23). To determine if sialic acid availability plays a role in the direct dissemination of pneumococci from the nasopharynx to the CNS, we incorporated N-acetylneuraminic acid (Neu5Ac) in our colonization model.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated previously that exogenous sialic acid promotes nasal colonization and lung invasion when given to mice postinfection, and the addition of sialic acid in vitro leads to the upregulation of NanA and NanB in pneumococci (22). Furthermore, it was shown that pneumococci have the ability to metabolize sialic acid, and when the locus responsible for sialic acid transport was deleted, colonization was inhibited in mice (23,24). This finding and evidence that bound sialic acid cleaved by influenza virus may exacerbate pneumococcal infection and contribute to invasive disease underscore the importance of sialic acid availability (25)(26)(27).…”
mentioning
confidence: 99%